1984
DOI: 10.1111/j.1600-0773.1984.tb01969.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimuscarinic Activity of Oxybutynin in the Human Plasma Quantitated by a Radioreceptor Assay

Abstract: The antimuscarinic activity of oxybutynin was measured as oxybutynin equivalents by a radioreceptor assay (RRA). The activity was studied in plasma samples of five volunteers after a single oral dose (10 mg) or after a single intravenous dose (28 micrograms/kg) of oxybutynin hydrochloride. The results were compared to the concentrations of the drug measured by gas liquid chromatography (GLC). Following oral administration, the maximum concentration measured by RRA was significantly higher (706 nmol/l) than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…In the in vitro experiment, it has previously been shown that DEOB exerts similar anticholinergic effect as its parent compound in the human detrusor (Barras et al, 1999;Waldeck et al, 1997). Therefore, it has been suggested that DEOB is largely responsible for the anticholinergic activity after oral administration of oxybutynin (Lindeke et al, 1981;Aaltonen et al, 1984). However, the in vivo anticholinergic effects of DEOB have been little characterized.…”
Section: Introductionmentioning
confidence: 96%
“…In the in vitro experiment, it has previously been shown that DEOB exerts similar anticholinergic effect as its parent compound in the human detrusor (Barras et al, 1999;Waldeck et al, 1997). Therefore, it has been suggested that DEOB is largely responsible for the anticholinergic activity after oral administration of oxybutynin (Lindeke et al, 1981;Aaltonen et al, 1984). However, the in vivo anticholinergic effects of DEOB have been little characterized.…”
Section: Introductionmentioning
confidence: 96%
“…Oxybutynin is rapidly absorbed following an oral dose, with peak plasma concentrations being achieved within an hour .4, 9 The absolute systemic availability is low, at around 6%, and large inter-individual variations in plasma concentration may occur.4 Practically none of the intact drug is recovered from the urine, suggesting that hepatic metabolism is the major pathway of oxybutynin inactivation.4~5 Plasma concentrations following therapeutic doses fall biexponentially, with an elimination half-life of around 2 h. In higher doses the elimination half-life is probably longer, due to a dose-related increase in the apparent volume of distribution.4 4 Possible adverse effects include a dry mouth, decreased sweating, urinary hesitancy and retention, mydriasis and failure of accommodation, tachycardia, palpitations, drowsiness, dizziness, insomnia, nausea, constipation, impotence, suppression of lactation and allergic skin reactions. Reported incidences of adverse effects vary from relatively high at 33% 6 to infrequent 7,8 at relatively similar therapeutic dose ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Oxybutynin and its metabolite, N-desethyloxybutynin, were analyzed in serum samples by capillary gas chromatography with mass-selective detection [Aaltonen et al, 1984] (HP-5790, column HP Ultra II, Hewlett-Packard, Little Falls, DE). Diazepam was used as the internal standard.…”
Section: Blood Sampling and Determination Of Serum Drug Concentrationsmentioning
confidence: 99%